Konsep Sombong dalam Al-Qur’an: Analisis Surah Luqman Ayat 18 dalam Tafsir Jalalain - Islamiati, Dian; Hamnah; Sunantri, Sri (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2024)
This research uses a type of literature research (Library Reseach) with qualitative methods. The sources in this study consist of two types, namely primary and secondary data sources. The primary data source is Tafsir Jalalain which amounts to 2 volumes, while secondary data consists of books or journals related to the theme, such as Minhâjul Qâshidin, Tazkiyatun Nafs, about the dangers of Takabur, thematic studies on Takabur in the perspective of the Qur'an and so on. In addition, data collection techniques in this study use library data sources with content analysis. As for data analysis techniques, researchers use a form of description analysis which is a form of research effort in telling problem solving based on data presentation, analysis and interpertation. The result of this study is the existence of a form of difference in terms of the definition of the meaning of arrogant contained in surah Luqman verse 18. The word consists of Marahân, mukhtal and fakhur. Marahân is an arrogant person with haughty feelings inside. Mukhtâl is an attitude of pretending to be arrogant when walking in front of others. As for fakhûr is defined as a person who is arrogant by boasting himself excessively. Based on the analysis of the interpretation of surah Luqman Verse 18 in Tafsir Jalalain, it can be concluded that one who pretends to be arrogant in walking with his face away, then the act is called Mukhtâl While one who walks on earth haughtily and feels arrogant, then the act is called fakhûr.